Pengaruh Kompetensi Pedagogik, Profesional, Kepribadian, dan Sosial terhadap Motivasi Kerja Guru UPT SPF SMK Negeri 2 Kota Parepare - Syarifuddin Syarifuddin; Irmawati Irmawati (Journal on Education, 2023)
This study aims to determine and analyze the partial and simultaneous effects of Pedagogic, Professional, Personality, and Social Competence on the Work Motivation of UPT SPF Teachers at SMK Negeri 2 Parepare City and the dominant variable influences the Work Motivation of UPT SPF teachers at SMK Negeri 2 Parepare City This research approach uses quantitative research. The research was conducted at SMK Negeri 2 Kota Parepare with a total population of 126 people. the sample in this study was carried out using the purposive random method, namely each subject teacher was represented by 2 teachers so that the total sample was 42 people. The data collection technique used questionnaires and the data analysis technique used multiple regression analysis techniques. Teacher Pedagogic Competence, Teacher Professional Competence, Teacher Personality Competence and Teacher Social Competence have a significant effect on teacher work motivation. UPT SPF SMK Negeri 2 Parepare City. Simultaneously Teacher Pedagogic Competence (X1), Teacher Professional Competence (X2), Teacher Personality Competence (X3) and Teacher Social Competence (X4) jointly affect the Work Motivation of UPT SPF teachers at SMK Negeri 2 Parepare City and the most dominant variable influencing the Work Motivation of UPT SPF teachers at SMK Negeri 2 Kota Parepare is the Teacher Social Competency variable.